Relative contributions of inferior petrosal sinus sampling and pituitary imaging in the investigation of children and adolescents with ACTH-dependent Cushing's syndrome. - Lienhardt, A; Grossman, AB; Dacie, J; Evanson, J; Huebner, A; Afshar, F; Plowman, P; Besser, G; Savage, M (2001)
Selective transsphenoidal microadenomectomy is the first line treatment of childhood Cushing's disease, with accurate preoperative localization of the corticotroph adenoma an important step in its investigation. Inferior petrosal sinus sampling (IPSS) for ACTH after CRH stimulation is a recognized investigation in adults, but there are few data in the pediatric age range. We report the relative contributions of IPSS and pituitary imaging in 11 patients, aged 10.7-18.8 yr, presenting with Cushing's disease. All underwent transsphenoidal surgery (TSS). IPSS was performed without complication. Sampling was from the inferior petrosal sinuses in 7 patients and the high jugular veins in 4 (patients 2, 4, 5, and 10). The central to peripheral ACTH (IPS/P) ratios were more than 2 (2.5-157.2) in 10 of 11 patients, confirming central ACTH secretion. In 3 patients with high jugular sampling, IPS/P ratio ranged from 2.5-21.1. In the fourth patient with high jugular sampling (IPS/P ratio, 0.95), a central adenoma was identified surgically, and the patient was cured after TSS. The interpetrosal sinus ACTH gradient (IPSG) was more than 1.4 (2.1-20.8) in 10 patients, indicating lateralization of ACTH secretion to the right side in 6 patients and to the left in 4. IPSG ratios were 2.1-8.5 in 3 patients with high jugular sampling. Pituitary imaging (computed tomography and or magnetic resonance imaging) was reported to identify an adenoma in 5 of 11 patients. At operation a tumor was visualized by the same surgeon in all 11 cases. In 9 patients with lateralization on IPSS, the correct side of the tumor was confirmed at surgery. In a 10th patient with a negative IPSG, a central tumor was present. Thus, IPSS gave a 91% prediction of correct tumor localization. In only 1 of 5 patients with an adenoma reported on pituitary imaging was this localization confirmed at surgery, a prediction rate of only 9%. After TSS, 8 patients were cured, 1 was in remission, and 2 required pituitary irradiation. In 73% of patients undergoing IPSS, localization of the adenoma was followed by surgical cure or remission. Pituitary scanning was therefore relatively unhelpful in localizing the adenoma. In experienced hands, however, IPSS was feasible in this age group, safe, and strongly predictive of the site of the adenoma, leading to a high rate of successful surgical outcome.